PENGARUH KOMITMEN ORGANISASIONAL DAN KOMPENSASI TERHADAP TURN OVER INTENTION DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PT. PERSADA LINES PEKANBARU - Rasyid, Angga Ahmad; Indarti, Sri (Jurnal Tepak Manajemen Bisnis, 2017)
This study aims to determine the effect of organizational commitment andcompensation concerning to turnover intention with job satisfaction as an interveningvariable in pt. persada lines pekanbaru, a national shipping company. This researchstart from february until december 2016. The population in this research are allmerchant seaman or ships sailor (ABK) which is all employed by PT. Persada LinesPekanbaru totaling 115 people. Selection of research sample conducted using samplingmethods saturated or census methods, which all members of the population sampled.The analysis tool of research is path analysis (path analysis). The survey resultsrevealed that Organizational Commitment has a significant direct effect on Turn OverIntention, compensation has a direct influence significantly to Turn Over Intention andJob Satisfaction has a direct influence on the turn over of Intention. While indirectlythrough Job Satisfaction, the Organizational Commitment has a significant effect onTurn Over Compensation Intention and indirectly have a significant effect on Turn OverIntention through job satisfaction. It can be concluded that the better OrganizationalCommitment and Compensation, then Turn Over Intention will decrease relevantly